2021
DOI: 10.3390/en14185820
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Stability Criteria of Network-Based Load Frequency Control of Power Systems with Time-Varying Delays

Abstract: The stability problem for load frequency control (LFC) of power systems with two time-varying communication delays is studied in this paper. The one-area and two-area LFC systems are considered, respectively, which are modeled as corresponding linear systems with additive time-varying delays. An improved stability criterion is proposed via a modified Lyapunov-Krasovskii functional (LKF) approach. Firstly, an augmented LKF consisting of delay-dependent matrices and some single-integral items containing time-var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Remark 3: In Jiang et al (2011), Ramakrishnan and Ray (2015), Yang et al (2017a), andFeng et al (2021), when the lower bound of the time delay is zero, the stability of the LFC power system has been studied and some stability criteria have been obtained. However, in some cases, the time-varying delay always varies within a non-zero interval.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remark 3: In Jiang et al (2011), Ramakrishnan and Ray (2015), Yang et al (2017a), andFeng et al (2021), when the lower bound of the time delay is zero, the stability of the LFC power system has been studied and some stability criteria have been obtained. However, in some cases, the time-varying delay always varies within a non-zero interval.…”
Section: Resultsmentioning
confidence: 99%
“…For the LFC power systems based on open communication networks, time-varying delays are unavoidable in data transmission between the controller and the plant (Jiang et al, 2011;Xu et al, 2017;Shen et al, 2020;Feng et al, 2021). A number of scholars have studied the communication time delay from the control center to the governor (Ramakrishnan and Ray, 2015;Yang et al, 2017a;Chen et al, 2020;Manikandan and Kokil, 2020), where the LFC power systems based on open communication networks can be modeled as time delay systems.…”
mentioning
confidence: 99%
“…Thus, for any non-zero 𝜔(t ) ∈ L 2 [0, ∞), we obtain E{‖Z (t )‖ 2 } < 𝛾‖𝜔(t )‖ 2 . Based on (15) and 𝜔(t ) ≡ 0, we can easily obtain ℑV (t , i ) < 0, and the asymptotic stabilizability of system (1) is established.…”
Section: Then By Consideringmentioning
confidence: 99%
“…Sun et al [13] demonstrated the global stability of the joint space of an excavator by applying a time-delay system control method. Some additional results in this field can be found in [14][15][16]. Thus, doing a controller design for Markov jump systems with time delay considered is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Such delays may have significant influences on the overall behavior of a dynamical system and result in oscillation, poor performance, and even instability. Therefore, the investigations about the stability of time-delay systems (TDSs) have become topical issues in the past few decades (see, e.g., [4][5][6][7][8][9]). In accordance with the dependence of stability conditions on delays, the criteria for stability of TDSs come in two varieties: those named delayindependent stability (DIS) criteria and those that are delay-dependent stability (DDS) criteria (see, e.g., [10][11][12][13]).…”
Section: Introductionmentioning
confidence: 99%